Analysis of a Fractional Reaction-Diffusion HBV Model with Cure of Infected Cells - Moussa Bachraoui; Khalid Hattaf; Noura Yousfi (Discrete Dynamics in Nature and Society)
In this paper, we propose a fractional reaction-diffusion model in order to better understand the mechanisms and dynamics of hepatitis B virus (HBV) infection in human body. The infection transmission is modeled by Hattaf–Yousfi functional response, and the fractional derivative is in the sense of Caputo. The global stability of the model equilibria is analyzed by means of Lyapunov functionals. Finally, numerical simulations are presented to support our analytical results.